Secure and scalable mobility management scheme for the Internet of Things integration in the future internet architecture. (30th July 2013) - Jara, Antonio J.; Kafle, Ved P.; Skarmeta, Antonio F.
Internet of Things is becoming a reality with the rapid development of communication technologies. This evolution presents an enrichment of the users' experiences, but also challenges regarding network scalability, security, privacy vulnerabilities, and mobility support. Mobility support for the Future Internet is focused on ID/Locator split architectures since the limitations of the current internet. This work analyses the security challenges for the HIMALIS (Heterogeneity Inclusion and Mobility Adaptation through Locator ID Separation) architecture for the particularities from the Internet of Things and the ID/Locator management messages vulnerable to attacks. This work proposes a secure and scalable mobility management scheme that considers the constraints from the Internet of Things, solving the possible security and privacy vulnerabilities of the HIMALIS architecture. The proposed scheme supports scalable inter–domain authentication and secure location update and binding transfer for the mobility process. The proposed scheme has been verified and evaluated successfully with the AVISPA framework.